Understanding Education
What purposes should education serve? Why does education matter? What should be done about education?These fundamental questions of value are not always seen as central to the sociology of education. However, this book argues that they are pivotal and provides a sophisticated and engaging invitation to the field that is designed to open up these important issues. It draws attention to the many points of disagreement that exist between major thinkers in the sociology of education, and the values on which their ideas are based. By involving readers in crucial questions about the potential contribution of sociology to education policies and practices, it aims to bridge the divide between education as it is talked about by academics, and the concerns of policymakers and educators who have to make practical decisions about what is to be done.The book reviews competing approaches in the sociology of education ÃƒÂ¢Ã¢â€šÂ¬Ã¢â,¬Å" structural functionalism, symbolic interactionism, Marxism, feminism, critical race theory and poststructuralism ÃƒÂ¢Ã¢â€šÂ¬Ã¢â,¬Å" and shows how these can be applied to major themes such as social reproduction, the politics of knowledge, multicultural education, identity and teachersÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ work. Throughout, the authors emphasise the importance of understanding social and educational values and the ways in which these underpin and impact upon the work of both academics and educators.